Challenges to and facilitators of occupational epidemiology research in the UK. Issue 7 (July 2020) - Sweity, Samaher; Sutton, Chris; Downe, Soo; Balaam, Marie-Clare; McElvenny, Damien M.
Highlights: Occupational Epidemiology field is facing many challenges affecting its current and future development. The key challenge facing the OE field is the progressive lack of resources and funding opportunities. Occupational Epidemiology community has become increasingly less influential and scattered. The OE field challenges are linked to social, economic and political factors such as deindustrialisation. Support from government and relevant stakeholders and effective communication are key facilitators to OE field. Abstract: This study investigated the challenges and facilitators of occupational epidemiology (OE) research in the UK, and evaluated the impact of these challenges. Semi-structured in-depth interviews with leading UK-based OE researchers, and a survey of UK-based OE researchers were conducted. Seven leading researchers were interviewed, and there were 54 survey respondents. Key reported challenges for OE were diminishing resources during recent decades, influenced by social, economic and political drivers, and changing fashions in research policy. Consequently, the community is getting smaller and less influential. These challenges may have negatively affected OE research, causing it to fail to keep pace with recent methodological development and impacting its output of high-quality research. Better communication with, and support from other researchers and relevant policy and funding stakeholders was identified as the main facilitators to OE research. Many diseases were initially discovered in workplaces, as these make exceptionally good study populations to accurately assess exposures. Due to the decline of manufacturing industry, there is a perception that occupational diseases are now a thing of the past. Nevertheless, new occupational exposures remain under-evaluated and the UK has become reliant on overseas epidemiology. This has been exacerbated by the decline in the academic occupational medicine base. Maintaining UK-based OE research is hence necessary for the future development of occupational health services and policies for the UK workforce.